2005
DOI: 10.1107/s1600536805040973
|View full text |Cite
|
Sign up to set email alerts
|

A non-centrosymmetric polymorph of Gd3RuO7

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean (Ru-O) = 0.009 Å R factor = 0.047 wR factor = 0.035 Data-to-parameter ratio = 30.4For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 4 publications
2
18
0
Order By: Relevance
“…These octahedra share corners forming one-dimensional chains which are oriented along the c-axis. The same space group Cmcm has been applied for Ln 3 RuO 7 (Ln = La-Gd) [2][3][4][5][6][7][8][9][10][11][12][13], Ln 3 ReO 7 (Ln = Pr, Nd, Sm-Tb) [14][15][16][17], Ln 3 OsO 7 (Ln = Pr, Nd, Sm-Gd) [11,18,19], Ln 3 TaO 7 (Ln = La-Nd) [20][21][22][23][24], Ln 3 IrO 7 (Ln = Pr, Nd, Sm, Eu) [25,26], Pr 3 NbO 7 [23] and Pr 3 SbO 7 [23]. For Ln 3 Sm-Ho) [20][21][22]24], Ln 3 SbO 7 (Ln = Y, Dy, Ho) [20,27], Ln 3 ReO 7 (Ln = Dy, Ho) [16,17], and Gd 3 NbO 7 [20], the space group C222 1 has been applied.…”
Section: Introductionmentioning
confidence: 99%
“…These octahedra share corners forming one-dimensional chains which are oriented along the c-axis. The same space group Cmcm has been applied for Ln 3 RuO 7 (Ln = La-Gd) [2][3][4][5][6][7][8][9][10][11][12][13], Ln 3 ReO 7 (Ln = Pr, Nd, Sm-Tb) [14][15][16][17], Ln 3 OsO 7 (Ln = Pr, Nd, Sm-Gd) [11,18,19], Ln 3 TaO 7 (Ln = La-Nd) [20][21][22][23][24], Ln 3 IrO 7 (Ln = Pr, Nd, Sm, Eu) [25,26], Pr 3 NbO 7 [23] and Pr 3 SbO 7 [23]. For Ln 3 Sm-Ho) [20][21][22]24], Ln 3 SbO 7 (Ln = Y, Dy, Ho) [20,27], Ln 3 ReO 7 (Ln = Dy, Ho) [16,17], and Gd 3 NbO 7 [20], the space group C222 1 has been applied.…”
Section: Introductionmentioning
confidence: 99%
“…These octahedra share corners forming one-dimensional chains which are oriented along the c-axis. The same space group Cmcm has been applied for Ln 3 RuO 7 (Ln = La ~ Gd) [2][3][4][5][6][7][8][9][10][11][12][13], 6 (ZFC) and field-cooled (FC) conditions. The former was measured upon heating the sample to 400 K under the applied magnetic field of 0.1 T after zero-field cooling to 1.8 K. The latter was measured upon cooling the sample from 400 to 1.8 K at 0.1 T.…”
Section: Introductionmentioning
confidence: 99%
“…Gemmill et al reported that Ln 3 OsO 7 (Ln = Pr, Sm-Tb) compounds undergo a structural phase transition from space group P2 1 nb to Cmcm with increasing temperature [19,20]. For Ln 3 RuO 7 , the same structural phase transition has been reported for Ln = Sm, Eu, and Gd [12,13]. We tried to analyze the X-ray diffraction data above the phase transition with the Cmcm model.…”
Section: Preparation and Crystal Structurementioning
confidence: 99%
“…For Gd 3 RuO 7 , we performed neutron diffraction measurements and reported that its low-temperature structure is described with space group P2/n [9]. Gemmill et al claimed that the observed structural phase transition of Ln 3 MO 7 (M = Ru, Os) is the one from space group Cmcm to P2 1 nb [12], and Ishizawa et al presented the detailed structural description [13]. For Ir-containing Ln 3 IrO 7 compounds, we showed that the observed structural phase transition is well described from space group Cmcm to P2 1 /n [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation